Chaos Before Order: Network Maps and Research Design in DTS - Tahir-Gürçağlar, Şehnaz (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThis paper explores how the notion of “network” can help expand the framework of translation historiography by providing a fuller inventory of translation-related phenomena in the initial phases of researching an attempt to supplement more critical approaches based on models of social causation. The case chosen for this study is the field of popular translated literature in Turkey during two different time periods, the 1960s and the 2000s, explored via the operation of a large publishing house, Altın Kitaplar (Golden Books). For the purposes of the paper, Altın Kitaplar is viewed as the focal point of a wide network composed of publishers, translators, authors, editors, readers, and government and literary institutions. A detailed review of its structure and activities offers a gateway into this network, which is traced in a number of directions, unveiling a series of interrelations with other fields in the publishing world that have largely gone unnoticed.